Morphology of immature stages and life cycle of Monotoma testacea Motschulsky (Coleoptera: Monotomidae) - Jałoszyński, Paweł (Zootaxa, 2021)
The egg, all three larval instars, and pupa are described for the cucujoid beetle species Monotoma (s. str.) testacea Motschulsky, which develops in decomposing plant matter. Adults and larvae were fed with baker’s yeast under laboratory conditions; this food source allowed for successful breeding of several generations. Detailed and illustrated descriptions of all immature stages are given. It is suggested that simple, pointed setae may represent a diagnostic character for Monotoma (s. str.), whereas clavate setae characterize Monotoma (Gyrocecis). Only minor differences in the number and patterns of setae were found between first, second and third larval instars, supporting observations of previous authors. Morphological differences are listed to distinguish between the three larval instars. An arrow-head aggregation of coarse asperities on the frontal region of the L1 larva, lacking in older instars, is hypothesized to be an egg-burster. Only 34–42 days elapsed from egg laying to emergence of the adult; the egg stage lasted 5–6 days; L1 larvae 2–3 days; L2 3–5 days; L3 2–5 days; the immovable prepupal stage 12–13 days; and the pupa 7–10 days. One female laid 1–5 eggs daily, averaging ~1.5 egg per day during her entire life; the total number of eggs in two independent cultures produced by one female accompanied by one male was 57 and 94.